Piperlongumine Alleviates Mouse Colitis and Colitis-Associated Colorectal Cancer - Huang, Jia-Rong; Wang, Sheng-Te; Wei, Meng-Ning; Liu, Kun; Fu, Jing-Wen; Xing, Zi-Hao; Shi, Zhi (Frontiers in Pharmacology, 2020)
Colorectal cancer is the one of most common and lethal cancer in the world. An important causative factor of colorectal cancer is ulcerative colitis. In this study, we investigated the therapeutic effects of piperlongumine (PL) on the dextran sulfate sodium (DSS)-induced acute colitis and azoxymethane (AOM)/DSS-induced colorectal cancer mouse models. Our results showed that PL could inhibit the inflammation of DSS-induced mouse colitis and tumor growth of AOM/DSS-induced mouse colorectal cancer by downregulation of proinflammatory cytokines COX-2 and IL-6 and EMT related factors β-catenin and snail expressions. These data suggested that PL might be an effective agent to treat colitis and colorectal cancer.